Politeness Strategies in Bahlil Lahadalia's Expressive Acts and Affective Color Responses on the Bukan Abuleke Podcast - Nahdliya Izzatul Mutammimah; Sumarti; Nurlaksana Eko Sasminto (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe Bahlil Lahadalia's politeness strategies, expressive speech acts, perlocutionary effects, and affective color responses in the Bukan Abuleke Podcast upload. Using a qualitative pragmatic approach, data were collected through listening and note-taking techniques, then analyzed using Brown and Levinson's taxonomy of politeness strategies and Searle's speech act theory. The results of the study revealed the dominance of Positive Politeness strategies (10 data) compared to Negative politeness, which reflects the speaker's intentional efforts to minimize social distance and build emotional closeness with the audience. Expressive acts were significantly dominated by the Praise category (8 data), which functioned as an instrument for building credibility through a narrative of personal resilience. The communication patterns found tended to be Direct and Literal (11 data), which effectively produced very strong Positive Responsive Verbal Nonverbal perlocutions (10 data). Affectively, the use of Humor (6 data) emerged as the main rhetorical instrument to defuse tension and respond to criticism diplomatically. The research conclusions indicate that Bahlil Lahadalia employs an adaptive communication style that integrates personal transparency with professional authority. This strategy successfully creates the image of a humanistic, inclusive, yet firm leader in disseminating state policies in the digital public sphere. These findings contribute to linguistic studies of public officials' rhetoric in new media formats.